2017
DOI: 10.1002/2017gl075126
|View full text |Cite
|
Sign up to set email alerts
|

Observational Inferences of Lateral Eddy Diffusivity in the Halocline of the Beaufort Gyre

Abstract: Using Ekman pumping rates mediated by sea ice in the Arctic Ocean's Beaufort Gyre (BG), the magnitude of lateral eddy diffusivities required to balance downward pumping is inferred. In this limit-that of vanishing residual-mean circulation-eddy-induced upwelling exactly balances downward pumping. The implied eddy diffusivity varies spatially and decays with depth, with values of 50-400 m 2 /s. Eddy diffusivity estimated using mixing length theory applied to BG mooring data exhibits a similar decay with depth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 38 publications
9
81
0
Order By: Relevance
“…Additionally, Yang et al () showed that the main balance of the time mean circulation is between the curl of the wind stress and eddy fluxes. Both Manucharyan and Spall () and Meneghello et al () showed that mesoscale eddies control variations in FWC by opposing the tendency of the Ekman pumping to deepen the halocline. Based on ice‐tethered profiler data, Zhao et al () showed that the greatest numbers of eddies were along the south and western boundaries of the BG, with the number of lower halocline eddies reaching a maximum in 2013–2014.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Yang et al () showed that the main balance of the time mean circulation is between the curl of the wind stress and eddy fluxes. Both Manucharyan and Spall () and Meneghello et al () showed that mesoscale eddies control variations in FWC by opposing the tendency of the Ekman pumping to deepen the halocline. Based on ice‐tethered profiler data, Zhao et al () showed that the greatest numbers of eddies were along the south and western boundaries of the BG, with the number of lower halocline eddies reaching a maximum in 2013–2014.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy diffusivity in the BG can vary significantly depending on the mean flow, stratification and as we will demonstrate in this study, continental slopes. Observational evidence from mooring data suggest that eddy diffusivity reaches values of about 600 m 2 /s (Meneghello et al, ), which is sufficient to counteract the Ekman pumping of about 10 m/year given the observed magnitudes of the halocline slopes. In the idealized eddy‐resolving model of Manucharyan and Spall (), which is characterized by a balance between eddy transport and Ekman pumping, an eddy diffusivity of 300 ± 200 m 2 /s were diagnosed, with higher values near gyre boundaries that have large halocline slopes.…”
Section: Introductionmentioning
confidence: 99%
“…The surface stress for the dashed blue line has been calculated using the ensemble average ice‐ocean relative velocity in equation . The gray shaded region on the x axis highlights the estimated range of 100–600 m 2 /s for eddy diffusivity in the BG (Meneghello et al, ).…”
Section: Analysis Of a General Circulation Modelmentioning
confidence: 99%
“…This mechanism is dubbed the Ice‐Ocean Governor by analogy with mechanical governors that regulate the speed of engines and other devices through dynamical feedbacks (see, e.g., Maxwell, ). The ocean velocity has long been included when calculating the ice‐ocean stress in numerical models (see, e.g., Hibler, ), but appreciation of the importance of this effect has been very recent (Dewey et al, ; Kwok & Morison, ; Meneghello et al, ; Meneghello, Marshall, Timmermans, et al, ; Meneghello, Marshall, Campin, et al, ; Zhong et al, ) following the publication of a data set that estimates sea surface height and surface geostrophic velocity in sea ice‐covered areas (Armitage et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation